2021
DOI: 10.1007/s11769-021-1220-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Groundwater Depth on the Soil Evaporation in Horqin Sandy Land, China

Abstract: The interactions between groundwater depth and soil hydrological processes, play an important role in both arid and semi-arid ecosystems. The effect of groundwater depth on soil water variations were neglected or not explicitly treated. In this paper, we combine a simulation experiment and a water flow module of HYDRUS-1D model to study the variation in soil evaporation under different groundwater depth conditions and the relationship between groundwater depth and evaporation efficiency in Horqin Sandy Land, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In view of the shortage of long-term gauged data concerning agriculture-use groundwater withdrawals in most of irrigated areas, there are few reports on the quantification of the response relationship of groundwater level and extracted groundwater water amount in large area of farmland. Furthermore, some studies showed that soil evaporation and groundwater recharge varied with buried depths of groundwater [33]. Groundwater level is governed by groundwater recharge and discharge.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the shortage of long-term gauged data concerning agriculture-use groundwater withdrawals in most of irrigated areas, there are few reports on the quantification of the response relationship of groundwater level and extracted groundwater water amount in large area of farmland. Furthermore, some studies showed that soil evaporation and groundwater recharge varied with buried depths of groundwater [33]. Groundwater level is governed by groundwater recharge and discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to conventional methods of quantifying soil water evaporation, such as direct measurements with a dissolved oxygen meter (Annelie et al, 2021; Laura et al, 2021), the equation method (Lehmann et al, 2019), the position flux method (Tingting et al, 2021; Xing et al, 2019), and the numerical simulation method (Li & Shi, 2021; Ma et al, 2019), the C–G model theoretically applies to any soil water evaporation conditions. Previous studies by Wei and Yong et al (Wei et al, 2015; Yong et al, 2020) have also validated the use of the C–G model for quantifying soil moisture evaporation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, standard methods for quantifying soil water evaporation include direct measurements using a lysimeter (Annelie et al, 2021; Laura et al, 2021), the formula method (Lehmann et al, 2019), the location flux method (Tingting et al, 2021; Xing et al, 2019), and numerical simulations (Li & Shi, 2021; Ma et al, 2019). These methods are simple in application and differ greatly from the complex and variable natural conditions, and do not fully consider the vertical transport of water in the soil, which is not conducive to an in‐depth understanding of the evaporation process and mechanism of soil water.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research conducted in arid climates (Taupin et al 1990, Woods 1990, Yang et al 2021, El Fergougui et al 2016 suggests that the climatic impact on shallow aquifer groundwater typically follows a two-zone pattern based on evaporation rate. Firstly, when the water table is close to the surface, the climatic effect is at its peak due to high evaporation rate.…”
Section: Spatio-temporal Behaviour Of Saturation Indexmentioning
confidence: 98%